2008
DOI: 10.1111/j.1469-0691.2007.01864.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic policy and prescribing strategies for therapy of extended-spectrum β-lactamase-producing Enterobacteriaceae: the role of piperacillin–tazobactam

Abstract: Therapy of infections caused by extended-spectrum beta-lactamase (ESBL)-producing bacteria with an antimicrobial to which they are resistant results in treatment failure, higher cost and increased mortality. The CLSI recommends reporting ESBL-producing strains of Escherichia coli, Klebsiella spp. and Proteus spp. as resistant to all penicillin, true cephalosporin and monobactam antimicrobials, but as susceptible to beta-lactam-beta-lactamase inhibitor combinations, including piperacillin-tazobactam, when they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…Piperacillintazobactam was noted as an antibiotic with a low resistance rate of 8% in inpatients. There are publications indicating that piperacillin-tazobactam may be used in the presence of ESBL-producing E. coli, and there are ongoing randomized controlled studies comparing its efficacy against these strains versus carbapenems (31)(32)(33)(34). The European Urology Association guidelines also describe piperacillin-tazobactam as an alternative antibiotic in the treatment of acute uncomplicated severe cases (30).…”
Section: Discussionmentioning
confidence: 99%
“…Piperacillintazobactam was noted as an antibiotic with a low resistance rate of 8% in inpatients. There are publications indicating that piperacillin-tazobactam may be used in the presence of ESBL-producing E. coli, and there are ongoing randomized controlled studies comparing its efficacy against these strains versus carbapenems (31)(32)(33)(34). The European Urology Association guidelines also describe piperacillin-tazobactam as an alternative antibiotic in the treatment of acute uncomplicated severe cases (30).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of ESBL producers, a variety of antibiotic classes must be considered a risk for inducing selective pressure, not just β-lactams and cephalosporins [88,91] although limiting widespread use of third generation cephalosporins has been shown to be effective in limiting ESBL producers [92]. Some data supports the switch of cephalosporins to piperacillin/tazobactam to try and curb the rising rates of such organisms [92,93].…”
Section: Infection Controlmentioning
confidence: 99%
“…This again reinforces the importance of recognising local resistance patterns. An antibiotic policy which takes this into account and restricts the use of broad spectrum agents (especially third-generation cephalosporins) is well recognised as key [28,90,92,93].…”
Section: Infection Controlmentioning
confidence: 99%
“…However, the results are conflicting due to study populations, geographical areas, selection of cases and controls and sample size. (38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Despite these statistical differences, some generalizations can be made.…”
Section: Risk Factors For Colonization /Infection With Esblmentioning
confidence: 99%
“…This may need to change with the advent of increasing antimicrobial resistance and increasing mortality associated with these CA-ESBL infections (44,59). Rodriguez-Bano examined CA-ESBL associated bacteremia and its features and found that in 95 patients with blood stream infections 7.3% were due to E.coli.…”
Section: Clinical Features Of Ca-uti Infections Caused By Esbl Pathogensmentioning
confidence: 99%